2013
DOI: 10.1016/j.humov.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Does the Animal Fun program improve motor performance in children aged 4–6years?

Abstract: The Animal Fun program was designed to enhance the motor ability of young children by imitating the movements of animals in a fun, inclusive setting. The efficacy of this program was investigated through a randomized controlled trial using a multivariate nested cohort design. Pre-intervention scores were recorded for 511 children aged 4.83 years to 6.17 years (M=5.42 years, SD=3.58 months). Six control and six intervention schools were compared 6 months later following the intervention, and then again at 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 36 publications
6
60
0
2
Order By: Relevance
“…The results are consistent with Wang's (2004) research where preschool children, through a creative kinetic program developed fundamental motor skills (Piek et al, 2012;Venetsanou & Kambas, 2004;Reilly et al, 2006;Kromboholz, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results are consistent with Wang's (2004) research where preschool children, through a creative kinetic program developed fundamental motor skills (Piek et al, 2012;Venetsanou & Kambas, 2004;Reilly et al, 2006;Kromboholz, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…As Hardy et al (2009), Linovena et al (2011 and Piek et al, (2012) support the acquisition of basic motor skills differs depending on gender, while Pollatou et al (2005) argues that there is no difference in gender in relation to motor development.…”
Section: Introductionmentioning
confidence: 97%
“…However, the population size seems sensible in comparison to other trials investigating motor activities in preschools. Piek et al included almost the same, 501 children [37], whereas Roth et al investigated the effect of a physical activity intervention in preschools in a somewhat larger sample of 709 children [38]. However, many studies have demonstrated statistically significant effects with considerably smaller samples [3942].…”
Section: Methodsmentioning
confidence: 99%
“…Activities involve the imitation of animals with the idea that fun and meaningful actions will encourage children to participate. A randomized controlled trial of the program with 511 children demonstrated significant improvement in motor skills at 18-month follow-up (Piek et al, 2012b). …”
Section: Introductionmentioning
confidence: 99%